High-intensity ultrasound treatment to produce and preserve the quality of fresh-cut kiwifruit - Yildiz, Gokcen; Yildiz, Gulcin; Khan, Moazzam Rafiq; Aadil, Rana Muhammad (Wiley, 2022)
In this study, high-intensity ultrasound (HIU), antibrowning chemicals (calcium chloride and ascorbic acid), water bath were used to avoid the browning of kiwifruit pieces, and the shelf-life of fresh-cut was measured (two weeks). The treated fresh-cut kiwi samples were evaluated in terms of color, enzyme activities, bioactive compounds, microbial, and sensory studies. The study has shown that HIU treatment restricted (p < .05) the microbial growth (bacteria, yeast, and mold) in fresh-cut kiwi samples at 4 degrees C. Moreover, kiwi samples exposed to HIU exhibited significant (p < .05) enhancements in bioactive metabolites as well as improvements in the physical features with the comparison of all other applications. Similarly, the lowest browning index values were observed for kiwifruit samples by HIU at the end of storage (180.04). Furthermore, the lowest scores for decay (0.5/3.0 and 0.9/3.0 on days 7 and 14, respectively) and off-odor (1/7 and 2/7 on days 7 and 14, respectively) were determined for the fresh-cut kiwifruit subjected to HIU. It has been proposed that HIU application is a possible choice to take the place of chemical and physical approaches to extend the product life and maintain quality characteristics in fresh-cut kiwifruit at cold storage conditions. Novelty impact statements A significant improvement in the quality of HIU-treated fresh-cut kiwifruits with the comparison of other chemical and physical treatments was achieved. This study contributed a novel method to develop HIU-treated fresh-cut fruit and vegetables with enhanced product quality and extended shelf life. In overall, processing of fresh-cut kiwifruits with a HIU treatment might be applied to get a high-quality and browning-free product.
Keywords: Juice; Technologies